Neuroprotective effects of taurine on SH-SY5Y cells under hydrocortisone induced stress (Research, Society and Development, 2021)
Alzheimer's disease (AD) is the most common, progressive and irreversible neurodegenerative disorder, characterized by memory loss, cognitive impairment and behavioral abnormalities. Although there is no cure, several study strategies seek to elucidate mechanisms of the disease. Recent studies address the benefits of taurine. Thus, the present study aims to analyze neuroprotective effects of taurine in human neuroblastoma (SH-SY5Y), using an in vitro experimental model of oxidative stress induced by hydrocortisone. This work showed for the first time that taurine can promote neuroprotection in SH-SY5Y under oxidative stress caused by hydrocortisone. Cell viability was evaluated using crystal violet and the evaluation of cell morphology was performed by scanning electron microscopy (SEM). The viability of SH-SY5Y pre-treated with taurine and stressed with hydrocortisone was preserved, compared to the stressed only group, which was also morphologically observed. Therefore, taurine can represent a considerable therapeutic candidate in the prevention of neurodegenerative diseases, such as AD.